2021
DOI: 10.1111/capa.12400
|View full text |Cite
|
Sign up to set email alerts
|

Local election campaign finance regimes in Canada: Toward a research agenda

Abstract: The regulation of election campaign donation, fundraising, expenditure, and advertising is an enduring object of study and reform. Compared to the federal and provincial levels, virtually no attention has been paid to Canadian municipal campaign finance regimes. This is surprising given the urban political economy literature’s focus on business influence on local politics and policy and evidence of corruption in Canadian local government. We take stock of Canadian campaign finance rules for municipal elections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The regulation of campaign finance is another area of the administration of municipal elections that has received some attention (Taylor & Vanhooren, 2021; Young & Austin, 2008). In Ontario, for example, research found that those who win typically spend more than those who do not win (Kushner et al, 1997), suggesting that campaign success is partially determined by the ability of a candidate to generate money and that a lack of regulation on campaign finances will lead to a “pay‐to‐win” election.…”
Section: Municipal Elections In Canada and The “Rules Of The Game”mentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of campaign finance is another area of the administration of municipal elections that has received some attention (Taylor & Vanhooren, 2021; Young & Austin, 2008). In Ontario, for example, research found that those who win typically spend more than those who do not win (Kushner et al, 1997), suggesting that campaign success is partially determined by the ability of a candidate to generate money and that a lack of regulation on campaign finances will lead to a “pay‐to‐win” election.…”
Section: Municipal Elections In Canada and The “Rules Of The Game”mentioning
confidence: 99%
“…Recent years have seen an increase in the study of municipal elections, including an exploration of public opinion through the Canadian Municipal Elections Study (McGregor et al, 2021), a database of election results (Lucas et al, 2021), an agenda on municipal campaign finance (Taylor & Vanhooren, 2021), and research on Internet voting (Essex & Goodman, 2020). However, fewer scholars have considered issues of how Canadian municipal elections are administered and regulated when compared with the body of research on Canadian federal elections, or comparative electoral management around the world (James et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The elected regional head candidates should be those who are solutive and bring a vision and mission to solve regional problems (Adams, 2010;Fleischmann & Stein, 1998;Warganegara & Waley, 2022). In practice, not all elected candidates are capable of solving regional problems (Marschall et al, 2011;Taylor & Vanhooren, 2021). In fact, some elected candidates are candidates who only have strong financial capital to influence people's choices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adequate finances can provide opportunities for candidates to engage with their voters (Briffault, 2006;Norris & Van Es, 2016). However, if excessive funds are used, it can lead to digression or irregularities in the organising of elections (Marschall et al, 2011;Taylor & Vanhooren, 2021). Similarly, the relationship between money and politics is a serious problem for governments with democratic systems (Benito et al, 2022;Noor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few, mostly quantitative studies on candidates' profiles (Couture Gagnon, et al, 2019;Tremblay, 2014). Except for their media coverage (Théberge-Guyon and Bourassa-Dansereau, 2019) and the oversight of election expenses (Taylor and Vanhooren, 2021), municipal election campaigns are non-existent in the field of Canadian political science. While observers regret the low turnout in Quebec municipal elections (around 40% on average), the issue of voter mobilization is not clearly addressed.…”
Section: Introductionmentioning
confidence: 99%